Sarcophages et coffrages en pierre des nécropoles de la Loire-Atlantique : une approche des stratégies d’approvisionnement en matériaux (ive-viiie siècle) - Alexandre Polinski (Archéologie Médiévale)
A survey of stone-supply strategies employed in Loire-Atlantique cemeteries during Late Antiquity and the Early Middle-Ages has provided a certain amount of new information both concerning the type and source of rocks used, and also the ways in which they were put to use. In particular, the importing of yellow-tufa sarcophagi, probably produced in the lower Vienne valley, has been identified. The Loire-Atlantique cemeteries use approximately the same supply sources as those in the Maine-et-Loire and from this point of view the lower Loire valley forms a coherent economic area.